Molecular testing for somatic cancer mutations: a survey of current and future testing in UK laboratories. Issue 3 (27th February 2008) - Wordsworth, S; Papanicolas, I; Buchanan, J; Frayling, I; Taylor, J; Tomlinson, I
Abstract : Background: Genetics clinical practice has paid limited attention to non-inherited aspects of cancer, namely mutations occurring during carcinogenesis. These somatic mutations are likely to be the primary determinants of cancer behaviour and treatment response, with a recent example being Her2/Neu gene status and response to Herceptin in breast cancer. Aim: To assess the feasibility of widespread testing of tumours by surveying UK histopathology and genetics laboratories. Methods: The questionnaire asked: which of the common cancers or other malignancies are routinely assessed; which molecular and cytogenetic methods are used; who orders and funds testing; what is the future demand for somatic testing; and what are the barriers to widespread testing? Results: Of 50 laboratories surveyed, 33 responded, 22 of which are currently using molecular tests. The survey shows that the most common tests are immunohistochemistry, fluorescence in-situ hybridisation and DNA testing of somatic mutations. Most laboratories predict testing will increase over the next 10 years, particularly for DNA testing using microarrays. Respondents perceived the main barriers to expanding molecular testing were a lack of laboratory funding and scientific evidence and testing not considered an NHS priority. Conclusion: These results provide important information for healthcare commissioners faced with managing demand for molecular testing of cancers.